Research Progress on the Biosynthesis and Applications of Functional Bile Acids - ZHENG Miao, CHANG Chao, SU Qi, CAI Chenggang, LU Yuyun, ZHAO Minjie, CAI Haiying (Shipin Kexue)
Bile acid (BA), as an important amphoteric sterol in bile, can regulate glucose and lipid metabolism and homeostasis, intestinal microecology, the intestinal barrier, inflammation, the immune system and the nervous system and other physiological functions through interaction with receptors and the intestinal flora, and consequently affect metabolism and nutritional health in the body. In this article, the synthesis pathways of the major new functional BAs are reviewed, and recent progress in research on their functional activity, chemical synthesis and biotransformation is systematically summarized. In addition, this article summarizes the functional studies of selected novel BAs (isodeoxycholic acid, isolithocholic acid (isoLCA), isoallodeoxycholic acid, and isoallolithocholic acid), as well as the microbial sources and catalytic properties of bioconvertases associated with the novel BAs and their potential for application in BA synthesis. Moreover, this article provides an outlook on the application potential of functional BAs in the fields of food and medicine, which provide a reference for the synthesis and transformation of new functional BAs and their comprehensive applications.